Implementasi Kebijakan Penanggulangan Bencana dan Mitigasi Banjir di Kabupaten Gresik - Retno Dwi Siswanto; Anggraeny Puspaningtyas (Faculty of Social and Political Science, 2023)
The flood disaster due to high rainfall and the overflow of the Lamong River which could not accommodate the incoming water discharge resulted in waterlogging in parts of Gresik Regency, especially those that occurred in Balongpanggang, Benjeng, Cerme, Menganti, and Driyorejo Districts. district. Knowing this, the Gresik Regency Government through the BPBD has made various efforts to minimize the impact that will be caused and optimize disaster management. The purpose of this research is to find out how the function of the Gresik Regency Regional Disaster Management Agency is implemented in flood emergency response. The method used in this research is descriptive qualitative with an in-depth approach. In this research using Policy Implementation Theory according to Edward III. The data used in this study were obtained from primary data and secondary data. The results showed that according to Edward III's theory, the implementation of the functions of the Gresik Regency Disaster Management Agency in disaster emergency response had been carried out properly and was also guided by Regional Regulation Number 7 of 2012 concerning Disaster Management.